2021
DOI: 10.1148/rycan.2021210048
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Whole-Body MRI versus FDG PET/CT for Lesion Detection in Participants with Myeloma

Abstract: A dvances in therapeutics that improve outcomes of patients with myeloma are key drivers for imaging developments. If bone marrow disease is detected early, and patients are treated according to clinical risk, then survival advantages are conferred (1-8). Histologic confirmation of clonal bone marrow plasma cells of greater than 10% in bone marrow or biopsy-proven plasmacytoma is a core requirement of diagnosis that is related to disease burden. However, for a diagnosis of multiple myeloma requiring treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…It was also shown that CT helps improve the diagnosis of bone involvement in patients with a low 18 F-FDG uptake (44,45). Comparison of the detectability of FLs showed that, overall, DW-MRI detects more FLs than does 18 F-FDG PET/CT (44)(45)(46). Reports agree that 18 F-FDG PET/CT appears to be superior for the detection of upper limb FLs, while DW-MRI seems better at analyzing the skull, the spine, and the pelvis (44,46).…”
Section: F-fdg Pet/ct Compared With Diffusion-weighted Mri For Baseli...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that CT helps improve the diagnosis of bone involvement in patients with a low 18 F-FDG uptake (44,45). Comparison of the detectability of FLs showed that, overall, DW-MRI detects more FLs than does 18 F-FDG PET/CT (44)(45)(46). Reports agree that 18 F-FDG PET/CT appears to be superior for the detection of upper limb FLs, while DW-MRI seems better at analyzing the skull, the spine, and the pelvis (44,46).…”
Section: F-fdg Pet/ct Compared With Diffusion-weighted Mri For Baseli...mentioning
confidence: 99%
“…Comparison of the detectability of FLs showed that, overall, DW-MRI detects more FLs than does 18 F-FDG PET/CT (44)(45)(46). Reports agree that 18 F-FDG PET/CT appears to be superior for the detection of upper limb FLs, while DW-MRI seems better at analyzing the skull, the spine, and the pelvis (44,46). A prospective study found that, although DW-MRI detected more FLs compared to 18 F-FDG PET/CT, there was no difference regarding bone disease diagnosis on a per patient basis, with an agreement of 1.0 (44).…”
Section: F-fdg Pet/ct Compared With Diffusion-weighted Mri For Baseli...mentioning
confidence: 99%
“…In addition, PET-CT is not uniformly applicable as approximately 10% of patients may have false negative results due to hexokinase deficiency. 32 Diffusion-weighted magnetic resonance imaging (MRI) is a more sensitive imaging modality for monitoring [33][34][35] but its widespread use is limited by capacity issues. 36 Extensive research has therefore been undertaken to identify more sensitive, non-invasive and practical ways to monitor therapeutic responses in the peripheral blood.…”
Section: R E V I E Wmentioning
confidence: 99%
“…In addition, PET‐CT is not uniformly applicable as approximately 10% of patients may have false negative results due to hexokinase deficiency 32 . Diffusion‐weighted magnetic resonance imaging (MRI) is a more sensitive imaging modality for monitoring 33–35 but its widespread use is limited by capacity issues 36 …”
Section: Introductionmentioning
confidence: 99%
“… 2 3 Evidence suggests that diffusion-weighted (DW) WB-MRI (WB-DW-MRI) is the most sensitive magnetic resonance technique for detecting marrow disease 4–8 and superior to fluorodeoxyglucose positron emission tomography/CT for the detection of small sites of disease and diffuse infiltration. 9 10 Therefore, WB-MRI is increasingly being adopted at centres worldwide for patients with myeloma. Treatment of high-risk patients is known to improve overall survival, 11 therefore improved diagnostic accuracy is likely to translate into improved patient selection for treatment and prolonged survival.…”
Section: Introductionmentioning
confidence: 99%